A Review: Nutrition Stimulation with in Ovo Feeding Technology for Optimization of Growth and Development of Prenatal and Postnatal Periods of Chicken - Daryatmo Daryatmo; Niken Ulupi; Rudi Afnan; Wahyuni Wahyuni (UNIVERSITAS ISLAM LAMONGAN, 2023)
The improvement in broiler chicken performance is currently thanks to the genetic selection, nutrition, maintenance management, and health and biosecurity programs that have succeeded in improving the maintenance performance of broilers.Â Such rapid development in the cycle after hatching is undoubtedly also influenced by the embryo's development or the prenatal phase. Unlike other mammals, the process of breeding poultry has its characteristics where the process of embryonic development occurs outside the body of livestock or inside poultry eggs. Chicken embryos rely heavily on the nutrients inside the egg, which provide the energy and amino acid makeup needed for the metabolic needs of the growing embryo during the 21-day incubation process. Chicken embryos are susceptible to a lack of energy during the hatching process. This deficiency can result in weak embryos and, in more severe conditions, embryo death and failure to hatch. The nutritional needs of embryos during incubation can be added to the egg with the in ovo feeding technique. The in ovo feeding technique is a technique that allows the addition of outside nutrients injected into the egg during incubation for the developmental and metabolic needs of the embryo, as well as to improve the nutritional status of the egg.Â Nutrition stimulation with in ovo feeding technique produces many benefits, such as increasing hatchability, hatching weight, immunity level, reduced bone system disorders, reduced morbidity and mortality after hatching, feed efficiency and weight gain.